Genotypic and Phenotypic Correlations between Leaf-Rust Disease and Leaf Morphology and its Ratio in Arabica Coffee - Sabam Malau (Institut Pertanian Bogor, 2020)
Selection parameter in coffee breeding for leaf rust (Hemeleia vastatrix) resistance is very important. Breeders used leaf-rust severity and leaf-rust incidence as parameters of direct selection. However, scientific proof is not yet available whether leaf morphology can be used as a parameter of indirect selection. The objective of this research was to seek the possibility of leaf morphology parameter and its ratio to be used as selection criteria through analyses of genotypic and phenotypic correlations of parameter of rust disease and parameter of leaf morphology and its ratio. The result revealed that genotypes showed significant variations in leaf-rust severity (5.21–25.84%), leaf morphology, and leaf-morphology ratio. Leaf length to leaf width ratio, leaf length to leaf area ratio, and leaf width to leaf weight ratio were not affected by the environment. Leaf-rust severity performed highly significant positive genotypic and phenotypic correlations the ratio of with leaf length to leaf area. For selection criteria, leaf-rust severity could be better used rather than leaf-rust incidence and branch-rust incidence. The ratio of leaf length to leaf area could also be used as an indirect selection criterion because the ratio showed a highly significant genotypic correlation with leaf-rust severity (rGab = 0.254**). However, the ratio of leaf length to leaf area is even better chosen for selection criteria rather than leaf-rust severity because the ratio was not affected by the environment. Keywords: fungus, Hemeleia vastatrix, indirect selection